FRI0278 IXEKIZUMAB IMPROVES SELF-REPORTED OVERALL FUNCTIONING AND HEALTH AS MEASURED BY THE ASAS HEALTH INDEX IN PATIENTS WITH NON-RADIOGRAPHIC AXIAL SPONDYLOARTHRITIS: 52-WEEK RESULTS OF A PHASE 3 RANDOMIZED, ACTIVE AND PLACEBO-CONTROLLED TRIAL (COAST-X). (2nd June 2020) - Kiltz, U.; Walsh, J. A.; Vargas, R. B.; Hunter, T.; Bolce, R.; Sandoval, D.; Liu Leage, S.; Leung, A.; LI, X.; Blue, E.; Braun, J.
Abstract : Background: Ixekizumab has demonstrated efficacy in treating signs and symptoms of patients with non-radiographic axial spondyloarthritis (nr-axSpA). 1 The Assessment of SpondyloArthritis International Society Health Index (ASAS HI) is a composite measure consisting of 17 dichotomous items to assess overall functioning and health in patients with spondyloarthritis. 2 Objectives: To assess health outcomes using ASAS HI in patients with nr-axSpA treated with ixekizumab (IXE) for 52 weeks. Methods: COAST-X (NCT02757352 ) was a 52-week, randomized, double-blind, placebo (PBO)-controlled study enrolling adults with an established diagnosis of axSpA (ASAS classification criteria, but not modified New York criteria for sacroiliitis), had Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) score ≥4, back pain score ≥4, inflammation (sacroiliitis on magnetic resonance imaging [MRI] per ASAS criteria) or an elevated C-reactive protein [CRP] level >5 mg/L), and inadequate response or intolerance to nonsteroidal anti-inflammatory drugs. Patients were randomized 1:1:1 to receive PBO or 80 mg IXE every 4 weeks (Q4W) or every 2 weeks (Q2W). Changing background medications or switching to open-label IXE Q2W, or both, was allowed after week 16 at investigator discretion. Change from baseline in ASAS HI (score 0-17 with higher score indicating worse health) was analyzed using logistic regression analysis at Weeks 0, 4, 8, 16, 36, and 52. For the ASAS HI, the smallest detectable change was calculated as 3.0. Patients having an ASAS HI score ≤5 were defined as being in a good health state. 3 Comparisons between IXE treatments and PBO were made using logistic regression analysis. Non-responder imputation was used for missing data. Patients who switched to open label IXEQ2W were considered non-responders after they switched. Results: At baseline, ASAS HI scores were similar between the three groups (PBO 9.0 ± 3.7; IXE Q4W 8.6 ± 3.4; IXE Q2W 9.6 ± 3.4). Significantly more patients receiving IXE Q4W versus PBO achieved ASAS HI score ≤5 at Week 16 (p<0.05; Fig. A). From Week 36 to 52, significantly more patients receiving IXE Q4W and Q2W achieved ASAS HI score ≤5 (p<0.05; Fig. A). Significantly more patients receiving IXE Q2W versus PBO achieved a clinically meaningful improvement in ASAS HI score ≥3 at Week 16 (p<0.05; Fig. B). From Week 36 to 52 significantly more patients receiving IXE Q4W and Q2W achieved a clinically meaningful improvement in ASAS HI score ≥3 compared with PBO (p<0.05; Fig. B). Conclusion: Ixekizumab improves overall functioning and health in patients with nr-axSpA as assessed by ASAS HI, with significantly more patients achieving good health status. References: [1]Deodhar A, van der Heijde D, Gensler LS, et al. Lancet . 2020; 395(10217):53-64. [2]Kiltz U, van der Heijde D, Boonen A, et al. Ann Rheum Dis . 2015;74(5):830-5. [3]Kiltz U, van der Heijde D, Boonen A, et al. Ann Rheum Dis . 2018;77(9):1311-7. Disclosure of Interests: Uta Kiltz Grant/research support from: AbbVie, Amgen, Biogen, Novartis, Pfizer, Consultant of: AbbVie, Biocad, Eli Lilly and Company, Grünenthal, Janssen, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, MSD, Novartis, Pfizer, Roche, UCB, Jessica A. Walsh Grant/research support from: AbbVie, Pfizer, Janssen, Consultant of: AbbVie, Novartis, Eli Lilly and Company, UCB, Ruben Burgos Vargas: None declared, Theresa Hunter Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Rebecca Bolce Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, David Sandoval Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Soyi Liu Leage Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Ann Leung: None declared, Xiaoqi Li Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Emily Blue Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Juergen Braun Grant/research support from: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, Eli Lilly and Company, Medac, MSD (Schering Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi- Aventis, and UCB Pharma, Consultant of: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Eli Lilly and Company, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis, and UCB Pharma, Speakers bureau: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Eli Lilly and Company, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis, and UCB Pharma